2010
DOI: 10.1088/1741-2560/7/6/066005
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder: a right temporal lobe syndrome?

Abstract: In a recent paper (Georgopoulos et al 2010 J. Neural Eng. 7 016011) we reported on the power of the magnetoencephalography (MEG)-based synchronous neural interactions (SNI) test to differentiate post-traumatic stress disorder (PTSD) subjects from healthy control subjects and to classify them with a high degree of accuracy. Here we show that the main differences in cortical communication circuitry between these two groups lie in the miscommunication of temporal and parietal and/or parieto-occipital right hemisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 26 publications
10
71
0
Order By: Relevance
“…However, several MEG studies have examined patients with PTSD during the resting state or during other cognitive tasks, and these studies have shown critical connectivity and/or oscillatory aberrations associated with the disorder. [27][28][29][30][31][32] The primary goal of the present study was to characterize the oscillatory dynamics that underlie working memory encoding and maintenance and to identify potential aberrations associated with PTSD by comparing the neural activity observed in veterans with PTSD to that of healthy participants. Our selection of a verbal working memory task was based on meta-analytic findings of stronger verbal than visual memory effects in individuals with PTSD 33 and is consistent with new meta-analytic findings of larger effects for verbal learning/ memory than for nonverbal learning/memory as well as for verbal learning over delayed recall, which may link these differences to verbal encoding deficits.…”
Section: J Psychiatry Neurosci 2016;41(4)mentioning
confidence: 99%
“…However, several MEG studies have examined patients with PTSD during the resting state or during other cognitive tasks, and these studies have shown critical connectivity and/or oscillatory aberrations associated with the disorder. [27][28][29][30][31][32] The primary goal of the present study was to characterize the oscillatory dynamics that underlie working memory encoding and maintenance and to identify potential aberrations associated with PTSD by comparing the neural activity observed in veterans with PTSD to that of healthy participants. Our selection of a verbal working memory task was based on meta-analytic findings of stronger verbal than visual memory effects in individuals with PTSD 33 and is consistent with new meta-analytic findings of larger effects for verbal learning/ memory than for nonverbal learning/memory as well as for verbal learning over delayed recall, which may link these differences to verbal encoding deficits.…”
Section: J Psychiatry Neurosci 2016;41(4)mentioning
confidence: 99%
“…We have previously demonstrated disease-specific deviations in SNI (Georgopoulos et al, 2007) and have proposed that SNI anomalies can be used as a diagnostic indicator Engdahl et al, 2010). In the present study we used least absolute shrinkage and selection operator (LASSO) regression (Tibshirani, 1996) to derive a diagnostic algorithm for PTSD based on MEG SNIs.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, impaired working memory, attention, and perceptual organization have been tied to alterations in neural synchrony in schizophrenia (Uhlhaas et al, 2009). Regarding PTSD, the most prominent deviations in SNI are hypothesized to underlie aberrant memory processing associated with re-experiencing symptoms Engdahl et al, 2010;James et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bryant et al (2010) implicated a marker role for the medial prefrontal cortex during non-conscious processing in PTSD. Engdahl et al (2010) reported that they classified with a high degree of accuracy PTSD participants and healthy controls using synchronous neural interactions as measured in magneto-encephalography.…”
Section: Posttraumatic Stress Disordermentioning
confidence: 99%